Manuk Abeghyan’s "Russian-Armenian Legal Manual Dictionary" - Abajyan, Anna (Bulletin of Yerevan University B: Philology, 2024)
"Russian-Armenian Legal Manual Dictionary" is the first professional dictionary related to Russian, which is a unique example of a collective intellectual work. Prior to the creation of this dictionary, there was no legal dictionary. Grabar Old Armenian was poor in legal terms which could be used by the authors, thus, it was necessary to create new words. More than 360 of the 1324 word-units in the dictionary (according to our calculations - AA) are either new terms: neologisms or new formations (abbreviations of often used words, modifications) or archaic words. Among the most important virtues of the dictionary are: a) The authors worked to put an Armenian word in front of each Russian term which will accurately express the meaning of the Russian term. b) The compilers of the dictionary, as much as is possible, avoided translating several Russian terms with the same Armenian word. "Russian-Armenian Legal Manual Dictionary" (1919) could stand the test of time, greatly contributing to the development of Armenian legal thought. Many words came into use, such as: հայց-claim, հայցվոր-plaintiff, վարձակալություն-rent, ավանս)կանխավճար-advance payment, арест личный- կալանք-personal arrest, property arrest -injunction, квитанция-անդորրագիր -receipt, контора-գրասենյակ-office, депозит - deposit-ավանդ, etc.